Gastrin, via activation of PPARα, protects the kidney against hypertensive injury. Issue 2 (29th January 2021) - Gu, Daqian; Fang, Dandong; Zhang, Mingming; Guo, Jingwen; Ren, Hongmei; Li, Xinyue; Zhang, Ziyue; Yang, Donghai; Zou, Xue; Liu, Yukai; Wang, Wei Eric; Wu, Gengze; et al.
Abstract: Hypertensive nephropathy (HN) is a common cause of end-stage renal disease with renal fibrosis; chronic kidney disease is associated with elevated serum gastrin. However, the relationship between gastrin and renal fibrosis in HN is still unknown. We, now, report that mice with angiotensin II (Ang II)-induced HN had increased renal cholecystokinin receptor B (CCKBR) expression. Knockout of CCKBR in mice aggravated, while long-term subcutaneous infusion of gastrin ameliorated the renal injury and interstitial fibrosis in HN and unilateral ureteral obstruction (UUO). The protective effects of gastrin on renal fibrosis can be independent of its regulation of blood pressure, because in UUO, gastrin decreased renal fibrosis without affecting blood pressure. Gastrin treatment decreased Ang II-induced renal tubule cell apoptosis, reversed Ang II-mediated inhibition of macrophage efferocytosis, and reduced renal inflammation. A screening of the regulatory factors of efferocytosis showed involvement of peroxisome proliferator-activated receptor α (PPAR-α). Knockdown of PPAR-α by shRNA blocked the anti-fibrotic effect of gastrin in vitro in mouse renal proximal tubule cells and macrophages. Immunofluorescence microscopy, Western blotting, luciferase reporter, and Cut&tag-qPCR analyses showed that CCKBR may be a transcription factor of PPAR-α, because gastrin treatment induced CCKBR translocation from cytosol to nucleus, binding to the PPAR-α promoter region, and increasing PPAR-α gene transcription. In conclusion, gastrin protects against HN by normalizing blood pressure, decreasing renal tubule cell apoptosis, and increasing macrophage efferocytosis. Gastrin-mediated CCKBR nuclear translocation may make it act as a transcription factor of PPAR-α, which is a novel signaling pathway. Gastrin may be a new potential drug for HN therapy.